2023
DOI: 10.4103/ijo.ijo_2054_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on intra-ocular pressure in patients with glaucoma

Abstract: Glaucoma is the second leading cause of blindness in the world, with an estimated 57.5 million people suffering from glaucoma globally. Treatment of glaucoma focuses on lowering intra-ocular pressure to prevent progression of visual field defects, which is the only proven method for treating this disease. Yoga practices are believed to lower intra-ocular pressure in the eyes and prevent further damage in patients with glaucoma. Therefore, this systematic review was planned to explore the available scientific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While relaxing techniques such as gazing at a flame, breathing, or meditating methods showed a significant reduction in IOP values in healthy and glaucoma individuals [6,7], an acute elevation in IOP, especially during head-down positions, has been observed before [9,16,17]. Although yoga seems to be a popular subject for scientific reports, there is only a small number of studies providing IOP values during yoga poses of glaucoma patients [18]. Between 2007 and 2021, merely one prospective study has been published, showing an acute elevation in IOP of 10 healthy and 10 glaucomatous participants during the same four yoga positions as we have investigated [8].…”
Section: Results In the Context Of The Existing Literaturementioning
confidence: 99%
“…While relaxing techniques such as gazing at a flame, breathing, or meditating methods showed a significant reduction in IOP values in healthy and glaucoma individuals [6,7], an acute elevation in IOP, especially during head-down positions, has been observed before [9,16,17]. Although yoga seems to be a popular subject for scientific reports, there is only a small number of studies providing IOP values during yoga poses of glaucoma patients [18]. Between 2007 and 2021, merely one prospective study has been published, showing an acute elevation in IOP of 10 healthy and 10 glaucomatous participants during the same four yoga positions as we have investigated [8].…”
Section: Results In the Context Of The Existing Literaturementioning
confidence: 99%
“…Research endeavors striving to identify such causative factors of NTG have led to the introduction of various theories encompassing heightened cellular and histochemical sensitivity to IOP, local or generalized vascular dysregulation, elevated IOP gradient across the lamina cribrosa, and cerebrospinal circulation impairment [ 39 ]. Recent studies propose that chronic low vascular perfusion, Raynaud’s phenomenon, migraine, nocturnal systemic hypotension, head down yoga, and over-treated systemic hypertension are the main causes of NTG [ 40 , 41 ]. An interesting aspect of NTG is that, despite moderate IOP, its treatment focuses on the reduction in IOP by circa 30% with demonstrated clinical efficacy [ 42 ].…”
Section: Glaucoma Etiopathologymentioning
confidence: 99%
“…In vitro studies have provided further insights into the cellular mechanisms underlying yoga’s effects. [ 43 ] It has been demonstrated that yoga practice reduced oxidative stress markers, improved mitochondrial function, and enhanced cellular viability in retinal cells. These findings collectively suggest that yoga interventions have the potential to improve optic nerve function and health through various mechanisms, including reducing cell death, enhancing blood flow, and mitigating oxidative stress.…”
Section: Yoga and Optic Neuropathy: Evidence From Preclinical To Clin...mentioning
confidence: 99%
“…This has been associated with improvements in ocular blood flow, oxygenation, increase in various neurotrophic factors, and nutrient delivery to the optic nerve. [ 22 43 53 ] Yoga is also known to have anti-inflammatory effects, as evidenced by reductions in pro-inflammatory cytokines and markers of inflammation in various conditions. [ 22 56 ] Inflammation plays a crucial role in optic neuropathy; yoga causes a decrease in inflammatory cytokines such as IL6, tumor necrosis factor-α, and NF-ƙβ and thus may help mitigate its detrimental effects.…”
Section: Mechanisms Of Yoga In Promoting Visual Healthmentioning
confidence: 99%
See 1 more Smart Citation